Recurrent painful ophthalmoplegic neuropathy: a report of two new pediatric cases - Günay, Çağatay; Edem, Pınar; Hız-Kurul, Ayşe Semra; Yaşar, Elif; Yiş, Uluç (The Turkish Journal of Pediatrics, 2022)
Background. Recurrent painful ophthalmologic neuropathy (RPON), formerly known as ophthalmoplegic migraine, is characterized by repeated attacks of one or more ocular cranial nerve palsies with an ipsilateral headache. While steroid therapy has been reported to be beneficial for attacks, no clear consensus on prophylactic treatments exists. We present two cases emphasizing the diagnostic significance of the loss of enhancement during the symptom-free period and valproate as a beneficial option in prophylaxis. Case 1. A 4-year-old girl presented with a one-week right frontal headache, vomiting and photophobia. Neurological examination revealed ptosis, oculomotor nerve paresis, and delay in light reflex in the right eye. Brain magnetic resonance imaging (MRI) revealed a 5.5 mm nodular enhancement in the cisternal part of the 3rd cranial nerve in the right premesencephalic area. The enhancement regressed after a 6-month symptom-free period. While propranolol, topiramate and flunarizine were inefficacious in prophylaxis, the patient responded to valproate prophylaxis and benefited from the administration of steroids for one week during the attacks. Case 2. A 7-year-old girl presented with a ten-day right-sided, throbbing headache in the frontal region, oneday eye deviation and double vision. Neurological examination revealed inward gaze restriction and ptosis in the ipsilateral eye to the headache. Brain MRI revealed a 4.5 mm, enhancing, nodular lesion in the 3rd cranial nerve lodge in the right perimesencephalic area. Her symptoms regressed in one week with dexamethasone and she received prophylactic propranolol. Neuroimaging findings disappeared after a 3-month symptom-free period. After valproate was added because of a relapse, she did not experience any further attacks. Conclusions. RPON is an uncommon disease in childhood with unknown etiology. On brain MRI with contrast during the symptom-free period, regression of the enhancement or complete resolution of the lesion are guiding features in the diagnosis. Valproate may have beneficial effects on RPON treatment.
Keywords: cranial nerves; headache; neuropathy; ophthalmoplegia; valproate